The Thoughts of KH. Djamaluddin Amin about the Integration of NU and Muhammadiyah Education in Islamic Educational Institution in Eastern Indonesia - Mujizatullah (Jurnal Pendidikan Islam, 2018)
This study aims to reveal the biography of KH Djamaluddin Amien and his thoughts. He was a generator figure of a social and educational movement that began with the emphasis on the development of educational facilities ranging from Kindergarten (TK / TPQ Raudhatul Athfal), Elementary School, Madrasah Tsanawiyah and Aliyah. In addition, he also built a mosque in Karaeng land, Bissoloro, Gowa District. The personality of KH Djamaluddin Amien as a figure of Muhammadiyah in South Sulawesi had its own characteristics especially in his thoughts on religious education, curriculum renewal, and teaching method by combining the teaching methods of KH Ahmad Dahlan and KH Hasyim Asy'ari. The character education model is through religious extracurricular by combining elements of religious study and general sciences in elementary and madrasah by using the classical system. The developed concept of education is multicultural, open to change, emphasis on discussion and dialogue, and social spirit. He was also active in teaching the yellow book by applying the Sorogan and Bandongan methods. The Kyai chose a simple life accompanied by visionary and consistent thoughts against the stagnation in thinking and doing good deeds.